Plasma membrane Ca2+-ATPase isoform 4b is phosphorylated on tyrosine 1176 in activated human platelets - Wan, Tina C.; Zabe, Martin; Dean, William L. (Thrombosis and Haemostasis, 2003)
Plasma membrane Ca2+-ATPase isoform 4b (PMCA4b) is phosphorylated on a tyrosine residue during platelet activation resulting in inhibition of its ATPase activity. We now report that tyrosine 1176 (Y1176) in the carboxyl (C-) terminal domain of PMCA4b is the phosphorylated residue. Two tyrosine residues located in the C-terminus of PMCA4b, Y1122 and Y1176 can be removed by calpain-dependent cleavage. This truncation removes all of the tyrosine phosphates added to PMCA during platelet activation. Sequence analysis indicates that Y1176 is a likely substrate for focal adhesion kinase (FAK), while Y1122 is not located in a tyrosine phosphorylation motif. This is the same residue we reported earlier to be phosphorylated by Src kinase in vitro. Thus we conclude that Y1176 is the only tyrosine phosphorylated during platelet activation. Results of co-immunoprecipitation, treatment with tyrosine kinase inhibitors and integrin inhibition experiments suggest that FAK is responsible for PMCA4b tyrosine phosphorylation during platelet activation.
Keywords: Platelet; plasma membrane Ca2+-ATPase; tyrosine phosphorylation; focal adhesion kinase